2019
DOI: 10.1016/j.snb.2019.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation electrochemical biosensor based on nitric oxide reductase immobilized in a multiwalled carbon nanotubes/1-n-butyl-3-methylimidazolium tetrafluoroborate nanocomposite for nitric oxide detection

Abstract: Nitric oxide (NO) has a crucial role in signaling and cellular physiology in humans. Herein, a novel third-generation biosensor based on the Marinobacter hydrocarbonoclasticus metalloenzyme (nitric oxide reductase (NOR)), responsible for the NO reduction in the denitrifying processes, was developed through the direct adsorption of a new nanocomposite (multiwalled carbon nanotubes (MWCNTs)/1-nbutyl-3-methylimidazolium tetrafluoroborate (BMIMBF4)/NOR) onto a pyrolytic graphite electrode (PGE) surface. The NOR di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…We will make use of this knowledge and specifically bind biomolecules on native and genetically functionalized S-layer fusion protein coated MWNTs (Figure 7a). CNTs and graphene have already shown great potential in the development of biosensors due to their huge surface area, great electron transfer rate, good electrical conductivity, and ability to immobilize biologically functional molecules, such as enzymes, aptamers, or receptors [12][13][14][15][16][17][18][19]. Concerning S-layers, a considerable amount of knowledge has accumulated concerning the fabrication of amperometric sensors for glucose [64] or sucrose [65] or of optical sensors for glucose too [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will make use of this knowledge and specifically bind biomolecules on native and genetically functionalized S-layer fusion protein coated MWNTs (Figure 7a). CNTs and graphene have already shown great potential in the development of biosensors due to their huge surface area, great electron transfer rate, good electrical conductivity, and ability to immobilize biologically functional molecules, such as enzymes, aptamers, or receptors [12][13][14][15][16][17][18][19]. Concerning S-layers, a considerable amount of knowledge has accumulated concerning the fabrication of amperometric sensors for glucose [64] or sucrose [65] or of optical sensors for glucose too [66].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins bound to the surface of CNTs are preferred in life-sciences because they provide a better biocompatibility and offer functional groups that may either be used for binding additional molecules in biosensor applications [12][13][14][15][16][17][18][19] or enable further chemical modifications, e.g., for the delivery of drugs, DNA and genes [20,21]. Nevertheless, although several proteins, such as bovine serum albumin (BSA), have already been successfully attached to CNTs through various physical or chemical methods, high resolution microscopical studies have demonstrated that their arrangement and density on the CNT surface and consequently the availability of functional groups varies considerably [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CNT surfaces are easily modified with different functional groups which facilitates the attachment of biological entities to develop biosensors. Therefore, all these characteristics have been extensively used in the development of electrochemical (bio)sensors [ 46 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Nanostructured Carbon-based (Bio)sensors For Pharmaceuticmentioning
confidence: 99%
“…Going a step further in the detection of NO, a third‐generation electrochemical biosensor based on NOR immobilized on a MWCNT‐BMIMBF4 composite was designed by Gomes et al. [ 252 ] in 2019. BMIMBF4 represents 1‐n‐butyl‐3‐methylimidazolium tetrafluoroborate which is an IL which combined with MWCNT and NOR to obtain the MWCNT/BMIMBF4 composite before subsequent immobilization of the MWCNT/BMIMBF4/NOR on PGE to get the PGE/MWCNT/BMIMBF4/NOR.…”
Section: Detection Of Nts Using Cnt‐based Sensorsmentioning
confidence: 99%
“…Nafion/MWCNTs-CS-AuNPs AP 7.6 0.019-54 [244] CAS/SOD/MP/MWCNT-PTTCA/ AuNPs/GCE AP 4.3 1-40 [246] 2011 GCE/MWCNT-CS-NiO AP 20 0.08-117 [247] MWCNT-CoTPPS/GCE CA 6600 6.6-13000 [ [252] current response in the presence of malathion using CV gave a LOD of 0.6 ng mL −1 . Another AChE modified MWCNT electrode was fabricated by Khan and Ghani (2012) for the determination of ACh and its metabolite simultaneously.…”
mentioning
confidence: 99%